2012
DOI: 10.1002/job.1811
|View full text |Cite
|
Sign up to set email alerts
|

Proactive socialization behavior in China: The mediating role of perceived insider status and the moderating role of supervisors' traditionality

Abstract: Summary This paper identified the dimensions of proactive socialization behavior among Chinese employees. We examined the mediating effects of perceived insider status on the relationships between proactive socialization behavior and socialization outcomes, and the moderating effect of supervisors' traditionality on the relationship between proactive socialization behavior and perceived insider status. Results from 280 newcomer–supervisor pairs supported the hypotheses that proactive socialization behavior was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 80 publications
1
87
0
3
Order By: Relevance
“…To obtain information or feedback, this not only gives employees and members of the organization a sense of intimacy and belonging, but also enables employees to more clearly understand the boundaries of the "insiders" and "outsiders" of the organization, and thus strengthens the employees' internal personalities. The perception of identity [6]. It can be inferred from this that the perception of organizational virtues helps to increase the awareness of employees' internal identities.…”
Section: H T Wangmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain information or feedback, this not only gives employees and members of the organization a sense of intimacy and belonging, but also enables employees to more clearly understand the boundaries of the "insiders" and "outsiders" of the organization, and thus strengthens the employees' internal personalities. The perception of identity [6]. It can be inferred from this that the perception of organizational virtues helps to increase the awareness of employees' internal identities.…”
Section: H T Wangmentioning
confidence: 99%
“…High morality organizations often make "deviations" conducive to their stakeholders and society [12], including caring for and helping their internal employees. Based on the principle of reciprocity, its employees are likely to repay the organization's gratitude by increasing their own recognition and commitment to the organiza- In addition, when employees perceive their identities as internal members of the organization, they will inspire their responsibility as an insider [6] and emotional commitment to the organization [19] [30], which in turn promotes employees' challenging organizational behavioral citizenship behavior. Based on this, the study further proposes the following assumptions:…”
Section: The Mediating Role Of Emotional Commitmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Proaktif olarak kurulan ilişkiler, yeni gelenin diğer grup üyeleriyle etkileşimini artırmakta ve işbirliği için gereken kişilerarası uyum becerilerini kazanmasına yardımcı olmaktadır (Wanberg & Kammeyer-Mueller, 2000). Grup üyeleriyle olan yoğun etkileşim, örgütsel çevrede yeni gelene yönelik pozitif izlenimin oluşmasını sağlamaktadır (Wang& Kim, 2013). Kuramcılar, sosyal bir grup ile bütünleşmenin durumsal bir kimlik kazanmayı içerdiğini ve sosyal etkileşimler yoluyla bu kimliği başarıyla kabul ettiren bireylerin örgütün bütünüyle 1 daha güçlü şekilde özdeşleştiğini ve yüksek seviyede bağlılık duyduklarını varsaymaktadırlar (Reichers, 1987;Kammeyer-Mueller& Wanberg 2003) 3.…”
Section: Sosyal Bütünleşmeunclassified
“…(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) In this search, only three studies were found within the nursing field. (9)(10)(11)(12) An investigation conducted in Turkey with 910 university hospital nurses resulted in a positive association between the proactivity of the nursing team and staff empowerment, revealing the importance of empowerment and individual differences to stimulate proactive behavior in organizations, especially when the teams plan its work in a participatory manner.…”
Section: Introductionmentioning
confidence: 99%